733. Incidence and Evaluation of the Change in Functional Status Associated with Respiratory Syncytial Virus Infection in Hospitalized Older Adults. (26th November 2018) - Branche, Angela; Granieri, Evelyn; Walsh, Edward; Finelli, Lynn; Greendyke, William; Falsey, Ann R; Barrett, Angela; Vargas, Celibell; Saiman, Lisa
Abstract: Background: Respiratory Syncytial Virus (RSV) causes severe respiratory illnesses in infants and older adults. Mortality disproportionately affects the elderly, can exacerbate chronic cardiopulmonary conditions and may result in loss of function. The purpose of this study was to determine the incidence of RSV infection in hospitalized adults and evaluate functional changes associated with RSV hospitalization in older adults ≥60 years. Methods: Adults ≥18 years of age admitted with an acute respiratory infection (ARI) or exacerbation of chronic cardiopulmonary disease (e.g. CHF, COPD, asthma) preceded by an ARI within 14 days were screened. Subjects were included if hospitalized for ≥24 hours with laboratory confirmed RSV and residing in two catchment areas (Rochester, NY and New York, NY). Illness history, comorbidities and demographic characteristics were collected at enrollment. Enrolled subjects ≥60 years underwent functional status evaluation retrospectively 2 weeks prior to hospitalization, at enrollment, discharge and 2 months using the Lawton–Brody Instrumental Activity of Daily Living (IADL) Scale (0–8), Barthel (ADL) Index (0–100), MRC Breathlessness score (1–5) and Mini-Cog instrument. Results: From October 2017 to March 2018, 2, 883 adults hospitalized with ARI were tested and 322 (11%) positive for RSV. Seventy-two adults ≥60 years underwent functional assessment. Mean age was 75 years, 53% were female and 58% demonstrated impaired cognition on admission. Five subjects died during hospitalization and one prior to 2-month follow-up. Interim analysis of 2-month functional assessment was available for 39 subjects. RSV illness resulted in acute functional loss in almost all patients. Although there were no statistically significant differences between mean pre-hospitalization and 2-month functional scores, IADL (6.7 vs. 6.0, P = 0.27), ADL (90.4 vs. 88.5, P = 0.67) and MRC (2.96 vs. 2.7, P = 0.57), 23% of subjects required a higher level of care at discharge. Additionally, RSV hospitalization resulted in decreased ADL scores in 36% of subjects and worsening respiratory function in 18% assessed at 2 months (figure). Conclusion: Older adults hospitalized with RSV infection demonstrate acute functional decline which may result in prolonged loss of function in some patients. Disclosures: A. Branche, Merck: Investigator, Grant recipient and Research grant. E. Granieri, Merck: Investigator, Research grant. E. Walsh, Merck: Investigator, Research grant. L. Finelli, Merck: Employee, Salary. A. R. Falsey, sanofi pasteur: Consultant and Grant Investigator, Consulting fee and Research grant. Gilead: Consultant, Consulting fee. Merck Sharpe and Dome: Investigator, Grant recipient. Janssen Pharmacueticals: Investigator, Grant recipient. Pfizer: Consultant, Research grant. Novavax: Consultant, none. A. Barrett, Merck: Investigator, Research support. L. Saiman, Merck: Investigator, Research grant.